Teaching business process management in cross-country collaborative teams using ERP - Jaeger, Bjoern; Rudra, Amit; Aitken, Ashley; Chang, Vanessa; Helgheim, B. (ECIS, 2011)
Academia generally employs a strict disciplinary model of education that results in a high degree of specialization within each discipline, while modern business environments require knowledge workers who can address problems and opportunities that cut across disciplines and on a global scale. This paper describes the development and evaluation of a new and innovative educational activity that responds to this requirement. The activity teaches business processes, business process management, and ERP-system skills by running a global supply chain role-play supported by a SAP ERP-system. It employs Kolb's experiential learning cycle to facilitate student learning about the issues associated with inter-organizational business process management supported by ERP-systems. A study wasundertaken with students from Australia and Norway forming teams executing inter-organizational business processes supported by SAP. The survey instrument used asked students to report perceived pre- and post- course knowledge and skills across five dimensions. Both Norwegian and Australian students showed a significant gain in perceived knowledge, and students involved in the inter-group (international) role-play showed better understanding of the transactional and management aspects of inter-organizational business processes than those who did not.